ANALISIS FAKTOR PENYEBAB DAN DAMPAK PERUBAHAN PENGGUNAAN LAHAN PERTANIAN PINGGIRAN KOTA YOGYAKARTA - Sudirman, Senthot; Irham, Irham; Hartono, Slamet; Maas, Azwar (Jurnal Sosial Ekonomi Pertanian, 2010)
The problems of the study are: (a) how the peri urban agricultural land use changes, (b) what factors influence land use cahange, (c) how the impacts of the land use changes on regional food lost, food availability, and the prospects of the farming sustainability in the peri urban area ofYogyakarta city. The objectives of the study are (a) to estimate the area and the rates of the peri urban agricultural land use change, (b) to estimate the factors influencing the land use change, and (c) to estimate the impacts of the peri urban agricultural land use change to the regional food lost, regional food availability, and the prospects of the farming sustainaibility in the peri urban area of Yogyakarta city..The data collection methods used in this study are: (a) Landsat TM satellite Images analysis, (b) digitally map overlaying on computer screen using Geographic Information System (GIS), (c) documentation of secondary data, (d) interview with quetionare as the guide, and (d) field observation. Data will be analyzed by using the mathematics, statistics, and econometrics equations specially multiple linear regression. Data will be presented as the table, diagram, curve and map.The results and conclusions of this research are (a) the changed of peri urban agricultural land use as long as 11 years from 1996-2007 are 922,17 ha in Sleman; 1.888,60 in Bantul; and 1.082,79 ha involving 47 sample of villages; the rates of land use changing is in negatif correlation with the the distance from the city, (b) the used econometric model in this research indicate a satisfaction goodness of fit with R2 of 0,895. Based on the analysis of variance, F-test, and t-test can be conclude that some factors i.e. Exhange Value of Agriculture Production (FPV), Technical Irrigated Agriculture Lands (IRG), the Precentage of Built Area to the Agriculture Lands (BCPr), People Density (Dens), Society Education (Edu), and the Agriculture Land Price (FLP) significantly influence to the rates of agriculture land changes, but the other factors i.e. the Precentage of agricultural lands to the village area (FLPr), Agriculture Lands Tax (FLT), Dummy of Bantul (DB), and Dummy of Kulon Progo (DKP) do not significantly at the Î± of 5-10%, and (c) the rates of agricultural lands changes have negative impacts to the regional food lost, regional food availability, and the prospects of the farming sustainability of peri urban agricultural lands. The number of regional food lost equivalent with 703,443 people, and the decreasing of regional food availability is equivalent with 572.259 people.Keywords: landsat image, land use change, overlay, peri urban